Needs Analysis and Design of Digital Electronics AR with the PjBL Model - Hartati; Putu Sudira; Dedi setiawan (Jurnal Penelitian Pendidikan IPA, 2025)
The rapid advancement of educational technology, particularly in vocational education, has opened new opportunities to address learning challenges in complex technical subjects. This study aims to analyze the needs and design Augmented Reality (AR)-based learning media for the Digital Electronics subject using the Project-Based Learning (PjBL) model. The AR media is designed to assist students in understanding abstract and complex concepts in Digital Electronics, such as logic circuits and digital systems, in an interactive and visual manner. The research method employed is Research and Development (R&D) following the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. Needs analysis results indicate that students face difficulties in understanding digital electronics concepts without additional visualization. Furthermore, both teachers and students expressed high interest in using AR technology to support a more effective and engaging learning process. PjBL-based AR media is expected to enhance students’ conceptual understanding and practical skills in Digital Electronics, as well as provide a deeper learning experience through applicative projects. By demonstrating this synergy between AR and PjBL, the study establishes a foundation for integrating immersive technologies into science and technology education, thereby enriching conceptual understanding while cultivating critical thinking, creativity, and other essential 21st-century competencies.